Accumulated knowledge and prevention practices in oral health - Efigênia Ferreira e FERREIRA; Nilce Emy TOMITA; Gisele da Silva DALBEN (Sociedade Brasileira de Pesquisa Odontológica, 2014)
This text begins by reflecting on health promotion and equity/ inequity. In health, inequity is understood as a political concept that has moral implications and that is committed to social justice. A discussion follows on some issues regarding the risk and prevention of diseases, still considered a hegemonic practice, and lack of experience in oral health-care, bearing in mind the concept of vulnerability. The risk is probabilistic and involves the mathematical chances of acquiring a disease in a certain group, whereas vulnerability addresses the potential of acquiring or not acquiring a disease in a certain environment. The need for systematic studies on determinants is stressed, with the ultimate goal of improving health and reducing inequities, and with the concern and political intention of including health equity in governmental policies.